The Role Of Islamic Educational Philosophy In Shaping Students' Spirituality - Wahyudi Wahyudi; Daffa Nayla Oktavia Hermawan Putri; Muhammad Yusron Maulana El-Yunusi (Wahana : Tridarma Perguruan Tinggi, 2025)
Spiritual is a trait related to something that is not material, for example, that is characteristic of humans, for example, intelligence, soul, sound frame. Spirituality also implies things related to the nature or quality or condition or mental and ethical tendencies of a person, as well as their original meaning that is contrary to the outer meaning or the actual meaning. The main goal of the Islamic educational philosophy is to produce individuals with great character, knowledge, and dynamic roles in society. Education in Islam aims to create human potential as a whole, both in-depth and educated, by combining science and devotional values. The teaching objectives of Islam also include the formation of a solid character, with a center on devotion, trust, equality, and mutual respect. Overall, the philosophy of Islamic Education greatly influences the spirituality of students because it directly teaches them to always connect every aspect of life with faith and devotion to Allah. With an education that is firmly rooted in spiritual and religious values, students not only gain academic knowledge but also experience profound spiritual development.